The Dynamics of Work Stress in the AI Era: Findings from an Educational Community Service Program - Rizqa Fithra Ramadhani; Rita Markus Idulfilastri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This Community Service Program (PKM) was conducted to address work-related stress experienced by partner institutions amid economic uncertainty and rapid digital transformation, particularly in the era of artificial intelligence (AI). The main issues identified included role ambiguity, job insecurity, and increasing demands for competency adaptation, which contribute to psychological stress, emotional exhaustion, reduced well-being, and declining work effectiveness. To respond to these challenges, the implementation team organized educational activities in the form of seminars and interactive sharing sessions titled “Thriving at Work in the AI Era: The Dynamics of Work Stress.” The program aimed to enhance participants’ understanding, awareness, and skills in identifying sources of work stress and applying adaptive stress management strategies. A participatory education method was applied, beginning with a pre-test and concluding with a post-test to assess changes in participants’ knowledge. The results showed a notable improvement in understanding, as reflected by a decrease in incorrect responses from 27.2% to 10.8% and an increase in correct responses from 72.8% to 89.2%. The implementation process consisted of three stages: preparation (team coordination, partner needs analysis, material development, and technical preparation), implementation (delivery of materials and interactive discussions), and evaluation and reporting. The mandatory outputs of this program include a PKM report and the publication of an article in a community service journal. Additional outputs involve dissemination through mass media and the development of a booklet intended for Intellectual Property Rights (IPR) registration.